UTILIZATION OF NATURAL COAGULANT SUBSTANCE (TAMARIND AND WINGED BEAN SEED) ON THE QUALITY OF TOFU WASTEWATER IN MUNTILAN, MAGELANG - Elpani, S. E.; Gunawan, M. J.; Aviventi, E.; Sabila, R. A. (Universitas Negeri Yogyakarta, 2019)
The aim of this study is to determine the effect of various mass in tamarind and winged bean seeds on pH, TDS, and COD in tofu factory wastewater. The research was conducted at the Chemistry Research Laboratory of FMIPA UNY in December 2018. The results showed that the addition of various mass in tamarind and winged bean seeds as much as 7, 9, and 11 grams of tofu factory wastewater had an effect on pH which increased from the initial condition of 2.5 to 2.6; 2.7; 2.8 in tamarind seeds, and 2.8; 2.9; 3.0 on winged beans. The COD test increased from the initial condition of 6619.20 mg / L to 7312, 64; 7880, 00; 8195.20 mg / L in tamarind seeds, and 9140.80; 10464.64; 9329.92 mg / L in winged bean seeds which have decreased again in the addition of 11-gram coagulant substance mass. TDS test has increased from the initial conditions of 1512 mg / L to 1715; 1736; 1848 mg / L in tamarind seeds, and 1890; 1988; 1855 mg / L in winged bean seeds.